112 Global Sagittal Flexibility Predicts Proximal Junctional Kyphosis After Spine Deformity Surgery. (1st April 2022) - Munjal, Vikas; Gibbs, David C.; Moranville, Robert; Keister, Alex; Mallory, Noah; Maggio, Dominic; Farhadi, Francis; Viljoen, Stephanus; Grossbach, Andrew J.
Abstract : INTRODUCTION: Adult spinal deformity (ASD) is a devastating disease with an estimated prevalence of 68%. Proximal junctional kyphosis (PJK) is a common complication of surgical intervention for ASD. With an incidence reported as high as 40%, PJK can lead to sagittal decompensation and necessitate reoperation. Few studies exist that examine the predictive utility of preoperative radiographic measurements in foreseeing postoperative PJK. METHODS: Demographic information, radiographs, complications, and patient-reported outcome measures (PROMs) were retrospectively analyzed from 109 patients who underwent long-segment thoraco-lumbar fusion at one midwest academic medical center. A Youden J-statistic was calculated based on ROC analysis of the difference between pre-operative standing and supine Sagittal Vertical Axis (ΔSVA), and the development of PJK at UIV + 2. Risk analysis was performed utilizing 2 × 2 contingency tables and Fisher's exact test. RESULTS: ROC analysis revealed an optimal ΔSVA threshold value of 38.8 mm. Patients with a ΔSVA > 38.8 were considered globally flexible, and those with ΔSVA ≤ 38.8 mm rigid. Rigid patients were noted to have a significantly higher change in their post-operative proximal junctional cobb angle (ΔPJCA p = 0.03) at the one-year time point, with a relative risk of 1.82 (Fisher's p = 0.0072). CONCLUSION: Based on this retrospective data, pre-operative global spinal rigidity portends an independently elevated risk (RR 1.82) for the development of PJK after ASD surgery. No differences in other complication rates or PROMs data was seen between groups. Our data collection is limited to a two year post-operative window. Future studies could look at longer timepoints to see if an increase in reoperation rates (extension of fusion surgery) is similarly seen.